DeGarmo's materials and processes in manufacturing - Degarmo, E. Paul; Black, J. Temple; Kohser, Ronald A. (John Wiley & Sons, 2018)
Authors J T. Black and Ron Kohser have continued this book's long and distinguished tradition of exceedingly clear presentation and highly practical approach to materials and processes, presenting mathematical models and analytical equations only when they enhance the basic understanding of the material. Updated to reflect all current practices, standards, and materials, the twelfth edition has new coverage of additive manufacturing, lean engineering, and processes related to ceramics, polymers, and plastics.